Mechanotherapy Reprograms Aged Muscle Stromal Cells to Remodel the Extracellular Matrix during Recovery from Disuse. Issue 3 (24th March 2022) - Hettinger, Zachary R; Wen, Yuan; Peck, Bailey D; Hamagata, Kyoko; Confides, Amy L; Van Pelt, Douglas W; Harrison, Douglas A; Miller, Benjamin F; Butterfield, Timothy A; Dupont-Versteegden, Esther E
Abstract: Aging is accompanied by reduced remodeling of skeletal muscle extracellular matrix (ECM), which is exacerbated during recovery following periods of disuse atrophy. Mechanotherapy has been shown to promote ECM remodeling through immunomodulation in adult muscle recovery, but not during the aged recovery from disuse. In order to determine if mechanotherapy promotes ECM remodeling in aged muscle, we performed single cell RNA sequencing (scRNA-seq) of all mononucleated cells in adult and aged rat gastrocnemius muscle recovering from disuse, with (REM) and without mechanotherapy (RE). We show that fibroadipogenic progenitor cells (FAPs) in aged RE muscle are highly enriched in chemotaxis genes ( Csf1 ), but absent in ECM remodeling genes compared to adult RE muscle ( Col1a1 ). Receptor-ligand (RL) network analysis of all mononucleated cell populations in aged RE muscle identified chemotaxis-enriched gene expression in numerous stromal cell populations (FAPs, endothelial cells, pericytes), despite reduced enrichment of genes related to phagocytic activity in myeloid cell populations (macrophages, monocytes, antigen presenting cells). Following mechanotherapy, aged REM mononuclear cell gene expression resembled adult RE muscle as evidenced by RL network analyses and KEGG pathway activity scoring. To validate our transcriptional findings, ECM turnover was measured in an independent cohort of animals using in vivo isotope tracing of intramuscular collagen and histological scoring of the ECM, which confirmed mechanotherapy-mediated ECM remodeling in aged RE muscle. Our results highlight age-related cellular mechanisms underpinning the impairment to complete recovery from disuse, and also promote mechanotherapy as an intervention to enhance ECM turnover in aged muscle recovering from disuse. Graphical Abstract: